2022
DOI: 10.3389/fagro.2022.831731
|View full text |Cite
|
Sign up to set email alerts
|

Shielding of Photosynthetic Apparatus by Consortia of Bacterial Endophytes in Tomato Plants Suffering From Fusarium Wilt

Abstract: Fusarium oxysporum is one of the most damaging plant pathogens causing Fusarium wilt in many plants leading to serious economic loss. The fungus colonizes the xylem, which leads to resistance in water flow in the plant thereby affecting the rate of photosynthesis. The present study focuses on the selection of bacterial endophytes isolated from tomato plants and evaluating their potential to antagonize Fusarium oxysporum in tomato in vivo. The results obtained indicated that two endophytic isolates, namely Pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In tobacco, it was established that CO 2 produced in roots was transported to shoots for photosynthesis via the vascular system instead of stomata (Andrade et al, 2022). It was suggested that endophyte colonization changed the host plant's photosynthetic apparatus, increasing the activity of light harvesting complexes and enhancing photosynthetic performance (Chaturvedi et al, 2022). Similarly, Liu et al (2021) indicated that seed endophytes stimulate PSII efficiency in plants.…”
Section: Discussionmentioning
confidence: 99%
“…In tobacco, it was established that CO 2 produced in roots was transported to shoots for photosynthesis via the vascular system instead of stomata (Andrade et al, 2022). It was suggested that endophyte colonization changed the host plant's photosynthetic apparatus, increasing the activity of light harvesting complexes and enhancing photosynthetic performance (Chaturvedi et al, 2022). Similarly, Liu et al (2021) indicated that seed endophytes stimulate PSII efficiency in plants.…”
Section: Discussionmentioning
confidence: 99%